2011
DOI: 10.1590/s0104-77602011000300017
|View full text |Cite
|
Sign up to set email alerts
|

Custo de produção das biomassas de eucalipto e capim-elefante para energia

Abstract: RESUMO:Nesse estudo, objetivou-se estabelecer o custo de produção da unidade energética gerada pela biomassa do eucalipto (Eucalyptus sp.), em diferentes tratamentos silviculturais, e pela biomassa do capim-elefante (Pennisetum sp.), e aplicar uma análise de sensibilidade para verifi car as infl uências de fatores como o tratamento silvicultural do eucalipto, a produção volumétrica de cada espécie, o custo da terra e a taxa de juros nos custos de produção analisados. Foi demonstrado que o tratamento do eucalip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…Data on the costs of SRWCs use in Latin America are limited to data available for Chile and Brazil [154,155]. In the Chilean case, Acuña et al [87,154] presented a detailed analysis of the production costs for the first two years for different plantation densities of Eucalyptus globulus.…”
Section: Production Costs Of Srwcs For Use As Bioenergymentioning
confidence: 99%
See 2 more Smart Citations
“…Data on the costs of SRWCs use in Latin America are limited to data available for Chile and Brazil [154,155]. In the Chilean case, Acuña et al [87,154] presented a detailed analysis of the production costs for the first two years for different plantation densities of Eucalyptus globulus.…”
Section: Production Costs Of Srwcs For Use As Bioenergymentioning
confidence: 99%
“…This analysis indicated that the main cost is incurred in the first year, during the SRWC establishment (plantation, fertilization and irrigation system), and then due to fertilization and weed control. For Brazil, Souza et al [155] presented a final SRWC production value between US $19-22 Mg -1 of SRWC biomass. A "Mg" is a land measure and corresponds to 1000 g or 1 ton.…”
Section: Production Costs Of Srwcs For Use As Bioenergymentioning
confidence: 99%
See 1 more Smart Citation
“…originated in the subtropical Africa and arrived in Brazil in 1920. It is currently cultivated in the five geographical regions of the country (Quéno et al, 2011). This species has aroused the interest of many researchers for serving as a feedstuff for animals (Valle et al, 2009;Lima et al, 2010), in addition to being a species with high plant biomass production, rapid growth, low cost, and high productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Eucalyptus aos 72 meses de idade. Os valores encontrados porLesle et al (2001) ficam próximos da faixa de produção dos clones de cana energia atingida para apenas um ciclo após aproximadamente 12 meses de sua colheita enquanto os valores apontados porQueno et al (2011) poderiam ser situações favoráveis em sistemas de produção que utilizam fundamentalmente cana como matéria prima através da redução dos custos de produção devido ao melhor aproveitamento das áreas de plantio e otimização dos processos de colheita e transporte. Além disso, em unidades que produzem etanol utilizando milho como matéria prima a introdução desses materiais poderia substituir outras fontes de biomassa, como eucalipto, fornecendo quantidades de biomassa semelhantes em praticamente um terço do tempo, como já ficou demonstrado no Produtividade de fibra, em t ha -1 , obtida ao longo dos períodos de coleta.…”
unclassified